Mesenchymal Stem Cell Transplantation for Liver Cell Failure: A New Direction and Option - Yantian Cao; Bangjie Zhang; Rong Lin; Qingzhi Wang; Jie Wang; Fangfang Shen (Gastroenterology Research and Practice)
Background and Aims. Mesenchymal stem cell transplantation (MSCT) became available with liver failure (LF), while the advantages of MSCs remain controversial. We aimed to assess clinical advantages of MSCT in patients with LF. Methods. Clinical researches reporting MSCT in LF patients were searched and included. Results. Nine articles (n=476) related with LF patients were enrolled. After MSCT, alanine aminotransferase (ALT) baseline decreased largely at half a month (P<0.05); total bilirubin (TBIL) baseline declined to a certain stable level of 78.57 μmol/L at 2 and 3 months (P<0.05). Notably, the decreased value (D value) of Model for End-Stage Liver Disease score (MELD) of acute-on-chronic liver failure (ACLF) group was higher than that of chronic liver failure (CLF) group (14.93 ± 1.24 versus 4.6 ± 5.66, P<0.05). Moreover, MELD baseline of ≥20 group was a higher D value of MELD than MELD baseline of <20 group with a significant statistical difference after MSCT (P=0.003). Conclusion. The early assessment of the efficacy of MSCT could be based on variations of ALT at half a month and TBIL at 2 and 3 months. And it had beneficial effects for patients with LF, especially in ACLF based on the D value of MELD.